Pengaruh Program Pengembangan Karier dan Motivasi Terhadap Kinerja Karyawan (Studi Pada Karyawan Bagian Pemasaran PT. Nyonya Meneer Semarang) - Mohamad Arifin; Apriatni Endang Prihatini; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2015)
In conducting its operational activities, Nyonya Meneer Semarang would want a good performance of the workers, especially the marketing. However this is not easy because the employees performance is affected by many factors. These factors include career development programs such as training and job mutation and other factors such as motivation.          The purpose of this study was to determine the influence of career development program in the form of training and mutation of work and motivation on employee performance of marketing Nyonya Meneer Semarang. This type of research is an explanatory research, with questionnaires, the study of literature and interviews. Tests carried out to employees of marketing with a population of 38 people using census method. This study used a qualitative and quantitative analysis techniques. Quantitative analysis using validity test, reliability test, simple and multiple regression analysis, the coefficient of determination, the significance test (t test and F test) with SPSS version 20.0 software for .          The results showed that the career development program through training and job mutation (X1), and motivation (X2), partially or simultaneously affect employee performance (Y) marketing. Motivation has a greater impact in influencing the performance of employees compared to the career development program.          Based on the results of this study, researchers gave advice to the Nyonya Meneer Semarang to pay more attention to theaspects of justice when providing employment mutation, and appreciation to the employees have the achievements that the performance of employees in marketing could be better.